(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Hamanyuk V. A. European Educational Standards as a Reference Point of Foreign Language Education in Ukraine. The article deals with the question of implementation of European educational standards to the Ukrainian system of foreign language high education. The frame programs for English and German for professional communication (integration of multicultural components and autonomic learning aspects) are analyzed.